Islamic Counseling Themes in Saheed Osupa’s Fuji Music: A Sharia-Based Review of the Kokoro Alate Album - Rauf Adeola Lateef; Asamu Rasheed Adebimpe; Adeyemo Timothy Olugbemiga (Walidem Institute and Publishing (WIP), 2025)
Objective: This study aims to examine the integration of Islamic counseling themes within Saheed Osupa’s Fuji music, with particular emphasis on the Kokoro Alate album, through a sharia-based analytical perspective. Theoretical framework: The theoretical framework of this research is grounded in Islamic counseling theory, which derives moral and psychological guidance from the Qur’an, Hadith, and Islamic ethical principles, including patience (sabr), repentance (tawbah), gratitude (shukr), accountability (taqwa), and moral responsibility. Literature review: Existing literature on religion and popular culture indicates that indigenous music genres often function as informal channels for moral instruction and spiritual reflection, yet limited attention has been given to Fuji music as a medium for Islamic counseling discourse. This study addresses this gap by situating Fuji music within the broader conversation on Islamic ethics and cultural expression. Methods: The research adopts a qualitative content analysis approach, focusing on selected lyrics from the Kokoro Alate album. The lyrics are examined to identify recurring counseling themes and to analyze their alignment with Islamic ethical values and sharia-oriented moral teachings. The analysis also considers the socio-cultural context of Yoruba Muslims, for whom Fuji music represents both cultural identity and religious expression. Results: The findings reveal that Saheed Osupa systematically embeds Islamic counseling messages within his lyrics through the use of metaphors, proverbs, and culturally familiar narratives. Themes such as self-reflection, endurance in adversity, moral restraint, family responsibility, and social justice are consistently emphasized. These messages function as moral reminders that encourage listeners to align personal behavior with Islamic principles while navigating contemporary social challenges. Implications: The study has significant implications for Islamic studies, counseling, and cultural discourse, demonstrating that popular music can serve as an effective medium for informal Islamic education and moral reform. It highlights the potential of culturally grounded art forms to transmit Sharia-based values beyond formal religious institutions. Novelty: The novelty of this research lies in its sharia-oriented reading of Fuji music as a form of Islamic counseling, offering a fresh perspective on how indigenous popular culture contributes to ethical formation and spiritual guidance among Muslim communities.